2017
DOI: 10.1155/2017/8395219
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Treatment Strategy for Complicated Chronic Wounds: Negative Pressure Therapy over Mesh Skin Graft

Abstract: Extensive skin defect represents a real problem and major challenge in plastic and reconstructive surgery. On one hand, skin grafts offer a practical method to deal with skin defects despite their unsuitability for several complicated wounds. On the other hand, negative pressure wound therapy (NPWT), applied before skin grafting, promotes granulation tissue growth. The aim of the study is to evaluate the improvement in wound healing given by the merger of these two different approaches. We treated 23 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Skin grafts are easy to perform and show reliable results . Typical colour mismatch due to basal hyperpigmentation can be observed but can be reliably treated with intense pulsed light …”
Section: Discussionmentioning
confidence: 99%
“…Skin grafts are easy to perform and show reliable results . Typical colour mismatch due to basal hyperpigmentation can be observed but can be reliably treated with intense pulsed light …”
Section: Discussionmentioning
confidence: 99%
“…Maruccia et al described faster healing, fewer dressing changes, and quicker maturity of mesh skin grafts when combined with NPWT. This combined treatment provides higher integration, better immobilization of the graft, expulsion of f luids, and a moist clean wound bed [35].…”
Section: Wound Healingmentioning
confidence: 99%
“…Maruccia et al, in 2016, reported a statistically significant reduction in pain scores and wound area in skin graft patients. This could be explained by faster healing and improved uptake of the graft, along with less frequent need for dressing changes [35].…”
Section: Pain Reliefmentioning
confidence: 99%
“…Liječenje rana terapijom negativnog tlaka (NPWT) pomoću vakuumom potpomognutog zatvaranja (VAC-a) pokazalo je dobre rezultate u liječenju kroničnih rana. Radi se o posebnom uređaju koji u rani stvara negativni tlak ispod 125 milimetara žive, a djeluje preko posebnih spužvi koje se umeću u ranu te se prema njoj i oblikuju 5 .…”
Section: Postupak Liječenja Vac Sustavomunclassified